2021
DOI: 10.1002/ejhf.2158
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase 3, a marker of the antagonist pathway of the renin–angiotensin–aldosterone system in patients with heart failure

Abstract: Recently, dipeptidyl peptidase 3 (DPP3) has been discovered as the peptidase responsible for cleavage of angiotensin (1-7) [Ang (1-7)]. Ang (1-7) is part of the angiotensin-converting enzyme-Ang (1-7)-Mas pathway which is considered to antagonize the renin-angiotensin-aldosterone system (RAAS). Since DPP3 inhibits the counteracting pathway of the RAAS, we hypothesize that DPP3 might be deleterious in the setting of heart failure. However, no data are available on DPP3 in chronic heart failure. We therefore inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Notably, we revealed here that lower circulating Dpp3 enzymatic levels are associated with a worse skeletal phenotype; conversely, in sepsis, cardiogenic shock, heart failure, and acute kidney injury the correlation goes in the opposite direction, with higher levels resulting in more severe disease and reduced survival rate [19][20][21][22][23][24][25]. In these conditions, angiotensin 2, the primary effector of the renin-angiotensin system (RAS), is recognized as the key substrate of Dpp3 activity and clinical evidence has been interpreted based on the modulation of the RAS by Dpp3, and the resulting impact on hemodynamics and on the physiology of the cardiovascular system.…”
Section: Discussionmentioning
confidence: 77%
“…Notably, we revealed here that lower circulating Dpp3 enzymatic levels are associated with a worse skeletal phenotype; conversely, in sepsis, cardiogenic shock, heart failure, and acute kidney injury the correlation goes in the opposite direction, with higher levels resulting in more severe disease and reduced survival rate [19][20][21][22][23][24][25]. In these conditions, angiotensin 2, the primary effector of the renin-angiotensin system (RAS), is recognized as the key substrate of Dpp3 activity and clinical evidence has been interpreted based on the modulation of the RAS by Dpp3, and the resulting impact on hemodynamics and on the physiology of the cardiovascular system.…”
Section: Discussionmentioning
confidence: 77%
“…10 Higher levels of circulating dipeptidyl peptidase 3 (DPP3) were related with mortality in patients with cardiogenic shock and DPP3 inhibition can improve haemodynamics. 11,12 Boorsma et al 13 showed that high DPP3 levels are associated with higher renin and aldosterone concentrations and poorer outcomes.…”
Section: Biomarkersmentioning
confidence: 99%
“…Elevated cDPP3 is associated with therapy refractoriness in cardiogenic shock [2]. Recently, cDPP3 levels were determined in 2314 advanced heart failure (HF) patients of the BIOSTAT-CHF observational cohort, revealing an increase in the combined endpoint of all-cause mortality and HF hospitalizations in the highest quartile [3].…”
mentioning
confidence: 99%
“…Consecutive patients with advanced HFrEF and GDMT were enrolled prospectively from the HF outpatient clinic at the Medical University of Vienna between February 2016 and December 2017. Routine laboratory parameters including NT-proBNP and active plasma renin concentration (ARC), and additionally a set of other established HF neurohumoral biomarkers-norepinephrine (NE), growth differentiation factor 15 (GDF-15), copeptin, big endothelin 1 (big-ET-1) and plasma neprilysin (NEP) activity-were measured in plasma by specific immunoassays and a fluorokinetic assay as described earlier [3]. Bioactive adrenomedullin (bio-ADM) and pro-enkephalin-A 119-159 (PENK) were determined in serum samples by the sphingotest ® assay.…”
mentioning
confidence: 99%
See 1 more Smart Citation